Drought tolerant wheat IND-ØØ412-7 is nutritionally equivalent to its Non-Transgenic Comparator - Miranda, Patricia V.; Iglesias, Bernardo Fabricio; Charriere, Maria Viviana; Burachik, Moisés (Taylor & Francis, 2023)
Expression of the HAHB4 sunflower transcription factor confers drought tolerance to wheat event IND-ØØ412-7 (HB4® wheat). After confirming the compositional equivalence of event IND-ØØ412-7 with conventional wheat, its nutritional similarity to its non-genetically modified (GM) counterpart was analyzed by performing a 42-day broiler feeding study. Isoenergetic diets containing 40% flour from wheat event IND-ØØ412-7, its non-GM counterpart Cadenza, and a commercial variety were included in the study. Broilers' performance was analyzed by measuring feed intake, weight gain, feed conversion, and time to reach 2.8 kgs. The yield was evaluated by carcass weight, breast meat, and abdominal fat. No differences were found between wheat event IND-ØØ412-7 and the non-GM counterpart. A few significant differences were found with the commercial variety which were associated with the genetic background, different from the other two materials. These results support the nutritional equivalence of event IND-ØØ412-7 with conventional wheat.